'Pre-endoscopy point of care test (Simtomax- IgA/IgG-Deamidated Gliadin Peptide) for coeliac disease in iron deficiency anaemia: diagnostic accuracy and a cost saving economic model'. Issue 1 (December 2016) - Lau, Michelle; Mooney, Peter; White, William; Appleby, Victoria; Moreea, Sulleman; Haythem, Ismail; Elias, Joshua; Bundhoo, Kiran; Corbett, Gareth; Wong, Liam; Tsai, Her; Cross, Simon; et al.
Abstract Background International guidelines recommend coeliac serology in iron deficiency anaemia, and duodenal biopsy for those tested positive to detect coeliac disease. However, pre-endoscopy serology is often unavailable, thus committing endoscopists to take routine duodenal biopsies. Some endoscopists consider duodenal biopsy mandatory in anaemia to exclude other pathologies. We hypothesise that using a point of care test at endoscopy could fill this gap, by providing rapid results to target anaemic patients who require biopsies, and save costs by biopsy avoidance. We therefore assessed three key aspects to this hypothesis: 1) the availability of pre-endoscopy serology in anaemia; 2) the sensitivities and cost effectiveness of pre-endoscopy coeliac screening with Simtomax in anaemia; 3) whether other anaemia-related pathologies could be missed by this targeted-biopsy approach. Methods Group 1: pre-endoscopy serology availability was retrospectively analysed in a multicentre cohort of 934 anaemic patients at 4 UK hospitals. Group 2: the sensitivities of Simtomax, endomysial and tissue-transglutaminase antibodies were compared in 133 prospectively recruited patients with iron deficiency anaemia attending for a gastroscopy. The sensitivities were measured against duodenal histology as the reference standard in all patients. The cost effectiveness of Simtomax was calculated based on the number of biopsies that could have been avoided compared to an all-biopsy approach. Group 3: the duodenal histology of 153 patients presenting to a separate iron deficiency anaemia clinic were retrospectively reviewed. Results In group 1, serology was available in 361 (33.8 %) patients. In group 2, the sensitivity and negative predictive value (NPV) were 100 % and 100 % for Simtomax, 96.2 % and 98.9 % for IgA-TTG, and 84.6 % and 96.4 % for EMA respectively. In group 3, the duodenal histology found no causes for anaemia other than coeliac disease. Conclusion Simtomax had excellent diagnostic accuracy in iron deficiency anaemia and was comparable to conventional serology. Duodenal biopsy did not identify any causes other than coeliac disease for iron deficiency anaemia, suggesting that biopsy avoidance in Simtomax negative anaemic patients is unlikely to miss other anaemia-related pathologies. Due to its 100 % NPV, Simtomax could reduce unnecessary biopsies by 66 % if only those with a positive Simtomax were biopsied, potentially saving £3690/100 gastroscopies. Trial registration The group 2 study was retrospectively registered with clinicaltrials.gov. Trial registration date: 13th July 2016; Trial registration number:NCT02834429 .